PEMBUATAN KARBON AKTIF DARI KULIT SALAK (Salacca Zalacca) DENGAN PROSES FISIKA MENGGUNAKAN UAP DENGAN PEMANAS MICROWAVE - Indah Sari; Uchi Inda Purnamasari; M. Turmuzi Lubis (Jurnal Teknik Kimia USU, 2017)
This study aimed to determine the best adsorption capacity, compounds contained in activated carbon and burn off that produced. In this study, activated carbon have been prepared from the bark of Salacca zalacca by physically activating using a microwave. The 70 gram bark of Salacca zalaccawas pyrolised in a furnace with flowing gas N2 with temperature 500 oC for 120 minutes followed by microwave activation at 2450 MHz with power 600 W, 800 W and 1000 W for 20 minutes, 40 minutes and 60 minutes. The results showed the best burn off on microwave power 1000 W with 60 minutes activation time of 90,25%. The best activated carbon adsorption capacity at 800 W microwave power for 20 minutes is 19,96 mg/g. The best allowanced percentage at 800 W microwave power with 20 minutes activation time is 99,82%. Characterization of Fourier Transform Infra-Red (FITR) showed the presence of C=O (carbonyl) bonds indicating the presence of carbon-active substances. After pyrolysis forms a C≡C (Alkuna) bond which indicated more carbon was produced. This is supported by the characterization of Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS) showing the surface morphology of rough and irregular activated carbon and the amount of carbon and oxide content on activated carbon of 44,44% and 28,54% sequentially.